2015
DOI: 10.1161/jaha.114.001255
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Cardioverter‐Defibrillator Therapy in Patients With Ventricular Fibrillation out of Hospital Cardiac Arrest Secondary to Acute Coronary Syndrome

Abstract: BackgroundSurvivors of ventricular fibrillation out of hospital cardiac arrest (VF‐OHCA) due to a potentially reversible cause such as acute myocardial infarction (MI) or ischemia are considered to be at low risk of recurrent arrhythmia. Implantable cardioverter defibrillators (ICD) are not routinely recommended in such patients. However, the outcome of these patients in the era of rapid coronary revascularization and ICD therapy is not known.Methods and ResultsWe examined the outcome of 114 consecutive surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…A pesar de contar con una muestra poblacional mayor, su resultado respecto a la sobrevida demostró resultados similares con nuestra experiencia. Con respecto al ritmo de paro, ellos describieron que los pacientes que presentan con Fibrilación Ventricular tienen un riesgo menor de muerte que los que se presentan con Taquicardia Ventricular, Asistolia o Actividad Eléctrica sin Pulso, haciendo referencia a descripciones en otros estudios 12,13 . En nuestro estudio solo un paciente falleció por un evento arrítmico, con lo cual creemos que la utilización del desfibrilador si impactó en la supervivencia de nuestra población.…”
Section: Resultsunclassified
“…A pesar de contar con una muestra poblacional mayor, su resultado respecto a la sobrevida demostró resultados similares con nuestra experiencia. Con respecto al ritmo de paro, ellos describieron que los pacientes que presentan con Fibrilación Ventricular tienen un riesgo menor de muerte que los que se presentan con Taquicardia Ventricular, Asistolia o Actividad Eléctrica sin Pulso, haciendo referencia a descripciones en otros estudios 12,13 . En nuestro estudio solo un paciente falleció por un evento arrítmico, con lo cual creemos que la utilización del desfibrilador si impactó en la supervivencia de nuestra población.…”
Section: Resultsunclassified
“…ICD benefit has been demonstrated in primary SCD prevention trials in patients with acute myocardial infarction and depressed ejection fraction < 35% [32] or when LV ejection fraction < 40% was ac-companied by non-sustained ventricular tachycardia and an inducible sustained ventricular tachycardia at the electrophysiologic study [26]. ICD implantation has been associated with improved survival in patients with ejection fraction > 35% who suffered SCD from an ischemic event [33]. However, since acute myocardial ischemia may be a reversible cause of cardiac arrest, SCD treated patients with obstructive CAD or ST elevations are currently not considered for secondary prevention and do not undergo ICD implantation [19].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study 15 showed that the rate of ICD therapy in patients with ischemic heart disease was 35 at 3 years, and patients with EF ≤ 35 at the time of discharge were at higher risk of recurrent ventricular arrhythmia. Furthermore, patients with EF 35 were declared at risk from ICD therapy in the rst eight months after OHCA.…”
Section: Appropriate Icd Therapy For Vf-ohca Due To a Reversible Causementioning
confidence: 95%
“…The recommendations around ICD implantation for VF-OHCA due to ischemic heart disease remain controversial. Madhavan et al 15 reported that ICD implantation with VF-OHCA due to ischemic heart disease did not have a statistically significant association with reduced allcause mortality after adjusting for potential confounders, but showed a trend towards signi cance. In contrast, Ladejobi et al 8 reported an association between ICD therapy and lower allcause mortality except for VF-OHCA due to ischemic heart disease.…”
Section: Icd Implantation For MI and Ischemic Heart Diseasementioning
confidence: 99%